Tobacco use is associated with increased postoperative pain and opioid use after reverse total shoulder arthroplasty: a retrospective cohort study. Issue 6 (14th November 2021) - Hartline, Jacob T.; Nelson, Clay G.; Eads, Ryan B.; Smith, Richard A.; Azar, Frederick M.; Brolin, Tyler J.; Throckmorton, Thomas W.
Abstract : Background: Tobacco use has been associated with negative outcomes in various orthopaedic procedures. To determine its effect on reverse total shoulder arthroplasty (rTSA), this study evaluated postoperative pain, opioid use, length of stay, complications, reoperations, and readmissions in the global 90-day episode of care after primary rTSA. Methods: A retrospective database search identified 279 patients with primary rTSA for multiple diagnoses. Patients were divided into current tobacco users (23), nonusers (150), and former users (106). All surgeries were performed with the same technique, implants, and primary surgeon. Gender, body mass index, preoperative diagnosis, laterality, and multiple comorbidities were analyzed as potential confounders. Results: Tobacco users reported significantly more pain at the preoperative ( P =0.013) and 12-week postoperative ( P =0.0068) visits; there were no differences in improvement of pain scores from preoperative to postoperative visits between groups ( P =0.58). Tobacco users also showed increased postoperative opioid use (2643 mg oral morphine equivalents) compared to nonusers (2121 mg) and former users (2015 mg; P =0.04). There were no significant differences in length of stay, complications, reoperations, or readmissions between groups ( P >0.05). Conclusions: Although no significant differences were noted in complications, reoperations, or readmissions, tobacco users reported higher levels of pain and required more opioid pain medication in the 90 days after rTSA compared with both nonusers and former users. Tobacco users experienced similar improvements in pain from the procedure as the other groups. Former users had similar postoperative outcomes as nonusers, suggesting that tobacco cessation can improve a patient's postoperative episode of care. Level of Evidence: Level III.